Physicochemical Characteristics of Anthocyanin Extract Powder from Black Rice Based on Maltodextrin and Skimmed Milk Powder Ratio as Encapsulant - Nurhidajah Nurhidajah; Ali Rosidi; Diode Yonata; Nurrahman Nrrahman; Boby Pranata (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Anthocyanins are bioactive components in black rice. Black rice anthocyanins are potent antioxidants, so they have the potential to be developed into functional food products. As a bioactive component, anthocyanins in extracts have low stability to environmental conditions such as light, temperature, and pH. Encapsulation process using the spray drying technique is known to protect and increase the stability of anthocyanin bioactive compounds. Maltodextrin (MDE) is widely used as a coating material in the encapsulation of anthocyanins using the spray drying technique with many advantages. However, skim milk powder (SMP) was found to encapsulate black rice anthocyanins efficiently. This study's general objective was to determine the effect of the ratio of MDE and SMP as an encapsulant on black rice extract powder's physical and chemical characteristics. The research method is an experimental type using a single factor Completely Randomized Design (CRD), which consisted of 6 treatments, namely the MDE:SMP ratio (100:0, 90:10, 80:20, 70:30, 60:40, and 50:50). The results showed that there was a very significant effect of the ratio of MDE and SMP on the physical and chemical characteristics of coated anthocyanin powder. MDE and SMP ratios of 50:50 resulted in coated anthocyanin powder's best physical and chemical characteristics. Keywords: Black rice extract, Coating material, Encapsulation, Physicochemical characteristics.